Zakres i tempo zmian w obrębie zasobów niematerialnych przedsiębiorstwa - Głuszek, Ewa (Scope and rate of intangible assets changes, 2006)
Intangible assets such as knowledge, products brands, reputation, or organizational culture are the main source of competitive advantage on present market. This information-based and knowledgebased resources of the firms are subject of permanent changes. The article studies a rate, scope and the controllability this changes.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 447-459